KEEFEKTIFAN LAGU SEBAGAI MEDIA BELAJAR DALAM PENGAJARAN PRONOUNCIATION/PENGUCAPAN - Muhimatul Ifadah; Siti Aimah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2012)
Language is one of basic human skills. For human beings, language is a means to fulfill their needs.The purpose of the study is to find out whether songs can be used as a media in learning English,especially pronunciation.The research used in the study is action research. In this study, the lecturer use songs as media tolearn pronunciation. In every treatment, there was a test administered after the treatment to evaluatethe result of the process. The test contained a list of words to be read, and also imperfect lyric of thesongs to be filled, and then the lecturer counted the correct numbers. The treatment were given ofsongs in speaking class, and conclusion will be taken after 4 meetings.The result of the research shown significant development. From the process, the students were able torecognize and used songs as a means to learn, not only for entertainment needs. The students wereable to analyze how message revealed from its lyrics, and found out the synonym of several words.Songs can be used as learning media because of its interesting and challenging aspects. Songs ease thestudents to imitate and store the information to their memories; however, it is definitely effective forteaching and learning process.